Supply Chain in Relation to Tourism and Crowd Management - Atheer N. SHAMI; Abdulaziz T. ALMAKTOOM (Communications of International Proceedings, 2022)
In the recent years, Saudi Arabia has been investing a large sum of resources in the tourism sector. For decades, Makkah has been the destination for many Muslims looking to visit the holy sight. With the pilgrims coming as well as tourists, the country is now facing the issue of whether or not it can handle the high amount of people visiting the country, especially during the summer where both tend to overlap. The aim of this research is to gain an understanding of supply chain applications in the tourism industry and exploration of crowd management with regards to tourism industry. The article also explores the advantages of using supply chain for crowd management in tourism industry, particularly with reference to the Saudi Arabia’s tourism industry, along with suggestions to integrate crowd management strategies in supply chain. This paper also highlights how the bloom of technology along with the cooperation of different companies can be used to lessen the effects of overcrowding. Due to this being a new issue and topic of discussion, the research done on the matter is limited and there are many new solutions that need to be inspected. With the limitations in mind, a qualitative method of analysis has been used to gather the below information.
Keywords: Supply chain; supply chain management (SCM); tourism industry; crowd management